Computational Efficiency Tradeoffs in Multimodal Alignment vs. Projection-Based Cross-Lingual NER - Assignee Research (Assignee Research, 2026)
Cross-lingual Named Entity Recognition (NER) leverages knowledge transfer between languages to identify and classify named entities, making it particularly useful for low-resource languages. We show that the data-based cross-lingual transfer method is an effective technique for crosslingual NER and can outperform multilingual language models for low-resource languages. This paper introduces two key enhancements to the annotation projection step in cross-lingual NER for low-resource languages. Fi
Machine-generated literature synthesis.